2001
DOI: 10.1097/00042728-200109000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Predictable Tissue Shrinkage During Frozen Section Histopathologic Processing for Mohs Micrographic Surgery

Abstract: background. When confronted with a histologic specimen that is appreciably smaller than the same tissue specimen immediately after acquisition, the Mohs surgeon is faced with two possibilities, namely that the tissue has either shrunken during laboratory processing or that the histologic specimen is incomplete due to the introduction of technical errors during embedding, cutting, or staining of the skin specimen. Because the entire objective of Mohs micrographic surgery is to precisely examine the entire surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Shrinkage of tissue is well documented to occur after excision and processing in skin and other tissues. [1][2][3][4][8][9][10] The 14% reduction in total specimen diameter after excision and fixation seen in this study is similar to our previous findings. 1 Between margin measurement and histological examination there is a variety of factors that might influence specimen size including initial tissue tension due to local anatomical factors, inherent tissue contractility, fixation effect and histological processing.…”
Section: Discussionsupporting
confidence: 91%
“…Shrinkage of tissue is well documented to occur after excision and processing in skin and other tissues. [1][2][3][4][8][9][10] The 14% reduction in total specimen diameter after excision and fixation seen in this study is similar to our previous findings. 1 Between margin measurement and histological examination there is a variety of factors that might influence specimen size including initial tissue tension due to local anatomical factors, inherent tissue contractility, fixation effect and histological processing.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, we suggest that the aforementioned factors significantly contribute to overestimation of TT using noninvasive imaging techniques such as HFUS. 17,18 In this study, the 95% limits of agreement, which showed discrepancies up to 71 mm for 20-MHz ultrasound and 30 mm for 100-MHz ultrasound, indicate a variable numerical agreement between HFUS and histology. In fact, 100-MHz ultrasound does agree better with histology than 20-MHz ultrasound.…”
Section: Discussionmentioning
confidence: 52%
“…The assessment of discrepancies between surgical and histopathological measurements of specimens is important in order to avoid repeat surgery and unnecessary follow-ups, besides legal implications with respect to the surgical margins around malignant tumors. 2 Surgical specimens of various human tissues, including prostate, breast, brain, oral cavity, colorectal, lung and carotid artery, 3,4 are known to undergo shrinkage, which has been attributed to the retractile properties of the specimens themselves and the action of formalin. 1,4,5 However, there have been few studies on cutaneous surgical specimens, and inconsistent findings have been published on their amount of shrinkage and on the potential role of formalin fixation.…”
mentioning
confidence: 99%
“…2 Surgical specimens of various human tissues, including prostate, breast, brain, oral cavity, colorectal, lung and carotid artery, 3,4 are known to undergo shrinkage, which has been attributed to the retractile properties of the specimens themselves and the action of formalin. 1,4,5 However, there have been few studies on cutaneous surgical specimens, and inconsistent findings have been published on their amount of shrinkage and on the potential role of formalin fixation. 1 -3,5-7 Results on the influence of factors such as sex, age, localization and diagnosis on the amount of shrinkage have also been controversial (Table 1).…”
mentioning
confidence: 99%